Electrical properties of methane hydrate + sediment mixtures. Issue 7 (30th July 2015) - Du Frane, Wyatt L.; Stern, Laura A.; Constable, Steven; Weitemeyer, Karen A.; Smith, Megan M.; Roberts, Jeffery J.
Abstract Knowledge of the electrical properties of multicomponent systems with gas hydrate, sediments, and pore water is needed to help relate electromagnetic (EM) measurements to specific gas hydrate concentration and distribution patterns in nature. Toward this goal, we built a pressure cell capable of measuring in situ electrical properties of multicomponent systems such that the effects of individual components and mixing relations can be assessed. We first established the temperature‐dependent electrical conductivity (σ) of pure, single‐phase methane hydrate to be ~5 orders of magnitude lower than seawater, a substantial contrast that can help differentiate hydrate deposits from significantly more conductive water‐saturated sediments in EM field surveys. Here we report σ measurements of two‐component systems in which methane hydrate is mixed with variable amounts of quartz sand or glass beads. Sand by itself has low σ but is found to increase the overall σ of mixtures with well‐connected methane hydrate. Alternatively, the overall σ decreases when sand concentrations are high enough to cause gas hydrate to be poorly connected, indicating that hydrate grains provide the primary conduction path. Our measurements suggest that impurities from sand induce chemical interactions and/or doping effects that result in higher electrical conductivity with lower temperature dependence. These results can be used in the modeling of massive or two‐phase gas‐hydrate‐bearing systems devoid of conductive pore water. Further experiments that include a free water phase are the necessary next steps toward developing complex models relevant to most natural systems.